Lhx9 Is Required for the Development of Retinal Nitric Oxide-Synthesizing Amacrine Cell Subtype - Balasubramanian, Revathi (Mol Neurobiol, 2017)
Amacrine cells are the most diverse group of retinal neurons. Various subtypes of amacrine interneurons mediate a vast majority of image forming and non-image forming visual functions. The transcriptional regulation governing the development of individual amacrine cell subtypes is not well understood. One such amacrine cell subtype comprises neuronal nitric oxide synthase (nNOS/bNOS/NOS1)-expressing amacrine cells (NOACs) that regulate the release of nitric oxide (NO), a neurotransmitter with physiological and clinical implications in the retina. We have identified the LIM-homeodomain transcription factor LHX9 to be necessary for the genesis of NOACs. During retinal development, NOACs express Lhx9, and Lhx9-null retinas lack NOACs. Lhx9-null retinas also display aberrations in dendritic stratification at the inner plexiform layer. Our cell lineage-tracing studies show that Lhx9-expressing cells give rise to both the GAD65 and GAD67 expressing sub-populations of GABAergic amacrine cells. As development proceeds, Lhx9 is downregulated in the GAD65 sub-population of GABAergic cells and is largely restricted to the GAD67 sub-population of amacrine cells that NOACs are a part of. Taken together, we have uncovered Lhx9 as a new molecular marker that defines a subset of amacrine cells and show that it is necessary for the development of the NOAC subtype of amacrine cells.